Gaya Bahasa Amr Bagi Konteks Haji Dalam Surah Al-Baqarah (Analysis of the Language Style of Amr in the Context of Hajj in Surah Al-Baqarah) - Rifa'in, Syakirah; Pa, Mat Taib; Samah, Rosni (Universiti Kebangsaan Malaysia Press, 2018)
This study discusses on the language style of amr concerning hajj, encompassing umrah as revealed in surah al-Baqarah. This study addresses two main objectives; firstly, to identify the form and functions of amr and secondly, to summarize the implicit meaning of the diverse forms of amr in the context of hajj including umrah in surah al-Baqarah. The study is designed using qualitative approach by employing text analysis based on Quranic exegeses by traditional and modern scholars. cAbbas (1997) Theory is applied for the first objective and the remaining objective is based on the Theory of al-Awsiy (1988) and al-Zuhayliy (1991). The findings of the study regarding hajj and umrah encompassed two forms of amr, which are ficl amr and uslub khabariy which means insyaiy. Three purposes of amr are discovered within this context and they are obligatory (wajib), warning (tahdid) and sunnah. With regards to the diverse types of indirect meaning of amr forms, this study found that ficl amr is used as a strong and firm way to reflect the intensity of command in explaining fundamental matters. Uslub khabariy which is referred to as insyaiy, is used subtly because it involves complicated matters. In conclusion, the forms of amr that have been used in specific contexts and circumstances have its own unique and implicit meanings. Thus, it is a good starting point to extend the scope of the present study to include other surah besides al-Baqarah.